2020
DOI: 10.1177/0265407520964870
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child relationship quality and emotional adjustment among college students: The role of parental financial support

Abstract: Many emerging adults experience increases in well-being as they exit adolescence, but college students are at particular risk for emotional adjustment problems, including depression and anxiety. Although receiving financial support from parents may reduce stress and aid emotional adjustment, not all parents are able to provide financial support. Maintaining high-quality relationships with parents may be particularly important for emotional adjustment in these instances. The present study examined whether the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…Even though the company of parents was a primary support source during the pandemic, which played an important role in reducing the risk of depressive symptoms among students (31,52), the quality of company might have had a further impact on their mental health (53). We found that less support from family and disharmonious relationships with parents were risk factors for depressive symptoms among students, which was in line with previous findings (12,54,55). The results provided us with some insight into preventing depressive symptoms among college students during a pandemic event.…”
Section: Discussionsupporting
confidence: 90%
“…Even though the company of parents was a primary support source during the pandemic, which played an important role in reducing the risk of depressive symptoms among students (31,52), the quality of company might have had a further impact on their mental health (53). We found that less support from family and disharmonious relationships with parents were risk factors for depressive symptoms among students, which was in line with previous findings (12,54,55). The results provided us with some insight into preventing depressive symptoms among college students during a pandemic event.…”
Section: Discussionsupporting
confidence: 90%
“…Then, in the behavior association analysis module, combined with the clustering results and the original student data, combined the student behavior characteristics, and used the association rule mining technology to analyze, extract the frequent patterns between different behaviors, and find the association relationship between different behaviors. Then, the results of the student division module and the behavior association analysis module are displayed in the application layer through visualization technology for users to observe and analyze ( Lindell et al, 2021 ; Berman et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…An absence of parents' monetary contributions may be due to an overall lack of available income, or simply because a parent believes the student should be financially independent. This presence or absence of financial support has an impact on parent-student relationships, as college students who report receiving more financial support from parents also report more positive relationships with parents (Lindell et al, 2020).…”
Section: Parental Expectations Regarding Provision Of Financial Supportmentioning
confidence: 99%